NAVIGATING THE LABYRINTH OF STATE-OWNED ENTERPRISES DISPUTES IN INDONESIA: A QUEST FOR EFFECTIVE RESOLUTION MECHANISMS - Kairupan, Maralda H. (Transnational Business Law Journal, 2023)
This paper critically assesses the adequacy of mediation as an alternative dispute resolution (ADR) method for resolving disputes between State-Owned Enterprises (SOEs) in Indonesia. It also explores the potential of other ADR methods for more effectively resolving such disputes specifically tailored for SOEs disputes. The paper commences by providing an overview of the mediation concept as an ADR mechanism, exploring its advantages and disadvantages. It then delves into the characteristics of typical SOEs disputes and the audit concerns associated with them. Subsequently, the paper examines international and Indonesian mediation practices, scrutinising their effectiveness and applicability in the context of SOE disputes. It also identifies the potential obstacles to using mediation to resolve SOE disputes, considering the inherent concerns of SOEs in making decisions. Based on these findings, the paper recommends the adoption of adjudication as an alternative ADR mechanism for SOEs disputes, advocating for the establishment of an Adjudication Tribunal tasked with rendering fair, impartial, and efficient decisions. Finally, the paper proposes a regulatory adjustment by identifying the potential risks associated with adjudication and providing mitigation strategies.